Template Specify layer hardened cam shaft - Bretislav Skrbek; Věra Jirásková (e-Journal of Nondestructive Testing)
Definition of the thickness of the surface-hardened layer after induction heating according to ČSN EN. Description of the hardened layers of the cam shaft of a diesel or gas engine with 19 surface-hardened cams and bearings. Methods of direct and indirect determination of the thickness of hardened layers. The relationship of the visual estimation of the thickness according to the etched cut to the thicknesses according to the HV hardness curves. Possibilities of non-destructive methods to determine the thickness of hardening. An experiment with the magnetic spot method and the DOMENA device. Knowledge for practical use. The direction of further development.